Quantitative methods and the CFA - McDonald, Michael (Henry Stewart Talks, 2020)
Variations of investment statistics, Measures of central tendency, Coefficient of variation, Sharpe ratio, The importance of probabilities in investments, Multiplication, addition, total probability rules